Pengaruh Pengangguran, Investasi Dan Produk Domestik Regional Bruto (PDRB) Terhadap Jumlah Penduduk Miskin di Provinsi Aceh - Siska Yanti; Cut Putri Sari (Jurnal Ekonomi Regional Unimal, 2023)
This study aim  to know the influence the Unemployment, Investment, and Gross Regional Domestic Product (GRDP) to the Number of Poor People in 5 Districts/Cities in Aceh Province. The data used in this study is secondary time series data for the 5 year period 20172021. Methods of data analysis in this study using panel data regression analysis. The results of thestudy with a significance level of 5% show that unemployment has a positive and significant effect ion the number of poor people, investment has no significant effect ion the number of poor people and Gross regional domestic product (GRDP) has a negative and significat on the number of ipoor people in 5 districts/cities in Aceh province.